The Effect of Work Environment on Teacher Performance with Workload as a Moderating Variable in State Senior High School in Lhoksumawe City - Muhammad Denni; Yusniar Lubis; Fajar Rezeki Ananda Lubis (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
The many negative environmental influences are considered to have caused a decline in student achievement levels. Therefore, it is necessary to have strategies to improve student achievement. Therefore, this study will test whether there is an influence of the work environment on the performance of high school teachers with workload as a moderating variable at state high schools in Lhoksumawe City. Data collection uses quantitative methods. The results of the study indicate that the work environment has a positive effect on teacher performance and teacher workload at Lhoksumawe City High Schools. Likewise, workload also affects teacher performance, and then there is also a positive influence of the work environment on teacher performance mediated by teacher workload at Lhoksumawe City High Schools.